Universidade Aberta do Brasil como Política Pública e seus Reflexos na Democratização do Ensino Superior - Fabrício Germano Alves; Júllia Andrade de Castro (Revista Justiça do Direito, 2026)
This article examines the evolution of regulatory frameworks that consolidated Distance Education (DE) in Brazil, focusing on the Open University of Brazil (UAB) as a public policy. Using the hypothetical-deductive method and a qualitative approach, it analyzes the institutional trajectory of this modality with the aim of identifying advances in the democratization of university access in rural and interior regions, as well as the structural challenges that compromise educational equity and the effectiveness of the modality. The results indicate that, although UAB has significantly expanded opportunities for higher education in the country, critical problems persist, including high dropout rates, weaknesses in pedagogical quality according to national assessments (ENADE), and administrative challenges in the coordination between local learning centers and higher education institutions. The study concludes that consolidating this public policy requires overcoming these bottlenecks through infrastructure investment and policies aimed at access and digital inclusion in order to realize its potential as an instrument for democratizing access and promoting sustainable territorial development in accordance with constitutional mandates.